2022
DOI: 10.3390/biomedicines10030643
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 13-Week Personalized Lifestyle Intervention Based on the Diabetes Subtype for People with Newly Diagnosed Type 2 Diabetes

Abstract: A type 2 diabetes mellitus (T2DM) subtyping method that determines the T2DM phenotype based on an extended oral glucose tolerance test is proposed. It assigns participants to one of seven subtypes according to their β-cell function and the presence of hepatic and/or muscle insulin resistance. The effectiveness of this subtyping approach and subsequent personalized lifestyle treatment in ameliorating T2DM was assessed in a primary care setting. Sixty participants, newly diagnosed with (pre)diabetes type 2 and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…For instance, one study delivered a precision nutrition intervention [ 19 ] based on participants’ postprandial glucose responses measured through continuous glucose monitoring (a personalized postprandial-targeting [PPT] diet). Another study personalized the diet on the basis of diabetes subtypes [ 20 ], while another developed individual dietary plan including calorie restriction and specific exercise prescriptions intending to achieve a BMI ≤ 25 [ 21 ]. Yet another study reported using a personalized dietary intervention, but did not describe how it was personalized nor the participants’ characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, one study delivered a precision nutrition intervention [ 19 ] based on participants’ postprandial glucose responses measured through continuous glucose monitoring (a personalized postprandial-targeting [PPT] diet). Another study personalized the diet on the basis of diabetes subtypes [ 20 ], while another developed individual dietary plan including calorie restriction and specific exercise prescriptions intending to achieve a BMI ≤ 25 [ 21 ]. Yet another study reported using a personalized dietary intervention, but did not describe how it was personalized nor the participants’ characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…In a study by de Hoogh et al, 75% of the participants in the personalized intervention group experienced remission at 13 weeks, compared to only 22% of their usual care group peers [ 20 ]. In this study, seven subtypes of diabetes were identified on the basis of their beta cell function and the presence of hepatic and/or muscle insulin resistance: (1) reduced beta cell function (PB), (2) hepatic insulin resistance (HIR), (3) muscle insulin resistance (MIR), (4) a combination of muscle and liver IR (CIR), (5) PB and HIR, (6) PB and MIR, and (7) PB and CIR [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Full remission into a healthy glucose metabolism through lifestyle medicine is well achievable, especially in the early phase preceding the disease. Multiple studies, indeed, have shown that lifestyle medicine is only successful in achieving T2D remission in a pre- or less advanced stage of the disease, but often fails in persons who have a more advanced, irreversible stage of T2D, especially those with β-cell dysfunction or combined tissue insulin resistance [ 19 , 20 , 21 ]. Therefore, early diagnosis and intervention are essential for reducing the societal burden of T2D.…”
Section: Introductionmentioning
confidence: 99%
“…The second one is an intervention study, which evaluated a 13-week personalized lifestyle intervention in newly diagnosed type 2 diabetes mellitus. The results showed an improvement in type 2 diabetes mellitus parameters compared with patients who received usual care [ 10 ]. The final two studies are narrative reviews devoted to the treatment of diabetes mellitus.…”
mentioning
confidence: 99%